Emotional Control Strategy And Its Relationship To Psychological Skills For Futsal Players (Advanced) - Hussein, Ali Radhi Abdul; Al- Jubouri , Zainab Hassan Falih; Abbood, Adnan Mohsin (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
This study aims to examine the effect of the team teaching strategy on improving students’ offensive basketball skills. The research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 40 students randomly divided into two groups: the experimental group, which was taught using the team teaching strategy, and the control group, which was taught using conventional methods. The research instrument included tests on offensive basketball skills such as passing, dribbling, shooting, and lay-up. Data were analyzed using paired sample t-tests and independent sample t-tests, assisted by SPSS software. The results showed a significant improvement in the experimental group’s performance compared to the control group. These findings indicate that the team teaching strategy is effective in enhancing students’ learning outcomes in basketball, especially in developing offensive skills. The collaborative approach between teachers allowed for more engaging, student-centered, and dynamic learning experiences. This study contributes to the field of physical education by offering an evidence-based teaching model that can be applied in practical classroom settings. Moreover, the findings provide valuable insights for educators, curriculum developers, and future researchers who aim to design and implement innovative, cooperative learning strategies to improve sports instruction in schools.